MANAJEMEN PERAWATAN KANKER DI KOMUNITAS SELAMA PANDEMI COVID-19 : LITERATUR REVIEW - Ifa Nofalia; Hartatik Hartatik (Universitas Muhammadiyah Kudus, 2022)
Coronavirus disease 2019 is a very dangerous virus because its transmission is very fast. The transmission is so fast that the WHO has declared the COVID-19 case a pandemic and in Indonesia it has been declared a national disaster. This article aims to conduct a comprehensive literature review to find out the management of cancer patient care during the Covid-19 pandemic in the community. The PRISMA approach is used and journal sources from several databases include Scopus, Science Direct, SAGE, CINAHL/EBSCO from 2019 to 2020. Boolean operators in the search process use AND and OR. Inclusion criteria for this literature search included research particles using human research samples, research articles using nursing management interventions in cancer cases, research journals in English and published in 2020. The exclusion criteria in this literature search were research studies with non-standard samples. humans, did not discuss cancer care management during the Covid-19 pandemic, research articles in the form of review studies and surveys, and journals published in unknown databases. Overall the review consisted of 14 articles, 4 articles using cohort studies, 4 case studies, 3 observational designs, 1 qualitative design, 1 prospective analysis and 1 pre-experimental. In this review, in summary, our research demonstrates that continuation of anticancer treatment during the COVID-19 pandemic appears safe and feasible, if adequate and strict infection control measures are enforced. Telemedicine is a great way for them because it sustains cancer care and reduces the risk of infection for both patients and caregivers.